2005
DOI: 10.1002/mar.20069
|View full text |Cite
|
Sign up to set email alerts
|

Advertising weak and strong brands: Who gains?

Abstract: The authors present an empirical study that compares advertising for a weak brand and advertising for a strong brand. The results indicate that brand attitude and purchase intention for the weak brand are higher when subjects cannot recall the ad. The opposite is found for the strong brand. Comparisons between single-brand ads and a joint ad reveal that ad-evoked brand recall increases for the weak brand in the joint ad and decreases for the strong brand. Furthermore, brand attitude and purchase intention are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 53 publications
3
24
0
Order By: Relevance
“…However, when two brands are featured in one advert, one brand is usually the primary focus while the other brand receives less attention (Wang and Muehling 2010). Our final hypothesis focuses on ad-context congruency that is the extent to which there is a match between the brand and context in which it is placed (Dahlén and Lange 2005). When the creative elements of an advertisement (e.g., visuals, slogans) are directly related to a brand's product category, ad context is considered congruent with the brand.…”
Section: Ad-context Congruency Of Co-branded Advertisingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when two brands are featured in one advert, one brand is usually the primary focus while the other brand receives less attention (Wang and Muehling 2010). Our final hypothesis focuses on ad-context congruency that is the extent to which there is a match between the brand and context in which it is placed (Dahlén and Lange 2005). When the creative elements of an advertisement (e.g., visuals, slogans) are directly related to a brand's product category, ad context is considered congruent with the brand.…”
Section: Ad-context Congruency Of Co-branded Advertisingmentioning
confidence: 99%
“…However, there is speculation that co-branding in advertising may actually hurt one or both brands promoted (Dahlén and Lange 2005;Romaniuk 2013). While not empirically tested, the presence of a second brand in advertising could trigger an interference effect, irrespective of the relationship between the brands, inhibiting audience recall of one or both brands (Bjork and Bjork 1996).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, if a company offers a brand with a higher value than their competitors' brands, a reduction in price will result in a greater increase in consumer purchasing than when competitors lower their price (Sivakumar and Raj, 1997). Although price discounts are efficient in terms of influencing consumers' attitudes and purchase intentions, they are very costly and may have detrimental effects, such as reducing consumers' reference prices and reducing company profitability (Blattberg et al, 1995;Dahlen and Lange, 2005). Alternatively, price discounts with a minimum purchase requirement are likely to benefit manufacturers and retailers.…”
Section: Price Discountmentioning
confidence: 98%
“…shows that consumers' pre-evaluations of a brand affect communication effectiveness (Dahlén and Lange, 2005;Wang and Muehling, 2012). In a CSR context, previous research has shown that stakeholders are particularly suspicious of companies' involvement in social causes if they have a poor reputation, have a poor existing CSR record, or belong to controversial industries (Bae and Cameron, 2006;Bhattacharya and Sen, 2004;Du et al, 2010;Strahilevitz, 2003;Yoon et al, 2006).…”
Section: The Moderating Role Of Brand Reputationmentioning
confidence: 99%